(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines the main types of lexical meanings of words in English. It focuses on denotational, connotational, emotive, stylistic, collocational, associative, reflected, thematic, and idiomatic meanings. The study highlights how these meanings function in communication and how context, usage, and culture influence understanding. The article also emphasizes the importance of mastering different types of lexical meanings for achieving fluency and communicative competence.